Role of copper homeostasis and cuproptosis in heart failure pathogenesis: implications for therapeutic strategies - Liu, Zhichao; Gan, Yongkang; Shen, Zhen; Cai, Siqi; Wang, Xizhen; Li, Yong; Li, Xiaofeng; Fu, Huanjie; Chen, Jinhong; Li, Ningcen (Frontiers in Pharmacology, 2025)
Copper is an essential micronutrient involved in various physiological processes in various cell types. Consequently, dysregulation of copper homeostasis—either excessive or deficient—can lead to pathological changes, such as heart failure (HF). Recently, a new type of copper-dependent cell death known as cuproptosis has drawn increasing attention to the impact of copper dyshomeostasis on HF. Notably, copper dyshomeostasis was associated with the occurrence of HF. Hence, this review aimed to investigate the biological processes involved in copper uptake, transport, excretion, and storage at both the cellular and systemic levels in terms of cuproptosis and HF, along with the underlying mechanisms of action. Additionally, the role of cuproptosis and its related mitochondrial dysfunction in HF pathogenesis was analyzed. Finally, we reviewed the therapeutic potential of current drugs that target copper metabolism for treating HF. Overall, the conclusions of this review revealed the therapeutic potential of copper-based therapies that target cuproptosis for the development of strategies for the treatment of HF.